Influence of Apical Patency on the Adaptation of the Master Filling Cone: A Cone-beam Computed Tomography Assessment - Diaz Zamalloa, Stephanie Isabel; Carvalho dos Santos, Caroline; Chilvarquer, Israel; Duailibi Neto, Eduardo Felippe; Caldeira, Celso Luiz (Iranian Endodontic Journal, 2023)
Introduction: This study aimed to evaluate if the apical patency can influence the adaptation of the master cone of gutta-percha, quantifying the volume of voids and areas at the last 2 mm of the working length (WL). Materials and Methods: Sixty distobuccal canals of extracted upper molars were divided into 3 groups (n=20) based on the patency length (A: passed 1 mm beyond the apical foramen (AF), B: at the AF and C: 1 mm short of the AF) with the Easy ProDesign Logic 25/0.01 file. Each group was subdivided into 2 subgroups (n=10) based on the WL established to prepare the root canal (1: 1 mm short of the AF or 2: at the AF) with the Easy ProDesign Logic 25/0.05 file. After the scan, void volumes were calculated from the last 2 mm of the WL and void areas at 0 mm, 1 mm and 2 mm of the last of WL, as well as the relation between the tip and taper of the master cone with the amount of void volume and areas. To investigate statistically significant differences, we used the Kruskal-Wallis statistical test. Results: There were more voids in volume when patency was achieved 1 mm beyond the AF and the root canal preparation was conducted at 1mm short of the AF (A1 group). Furthermore, the same group showed more voids areas, mainly on the last millimeter of WL. Conclusion: Achieving apical patency at 1 mm beyond the AF followed by instrumentation 1 mm short of the AF created more voids between the master gutta-percha cone and the root canal wall, especially on the last millimeter of WL.